Innovation and Inspiration: The Development of Inuktitut Syllabic Orthography - Harper, Kenn (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractIn the 1850's John Harden and E.A. Watkins, missionaries of the Church Missionary Society (CMS) to James Bay, began the work of adapting James Evan's Cree syllabic orthography to Inuktitut. Watkins' introduced the syllabic writing system to Inuit at Fort George and Little Whale River in 1855, and that same year Harden printed a small book of scripture verses in syllables on his press at Moose Factory. In 1865, at the request of CMS Secretary Henry Venn, Harden and Watkins met in conference in England and modified the syllabic system to allow a more precise rendering of both Inuktitut and Moose Cree. It remained for Edmund James Peck, who arrived in the diocese in 1876, to devote his attention to the translation of scripture into Inuktitut in Harden and Watkins' orthography. Only minor changes were made in the Inuktitut orthography until the major revision under the direction of the Inuit Cultural Institute in the 1970's.